Exploring the quality of life issues in people with retinal diseases: a qualitative study - Mallika Prem Senthil; Jyoti Khadka; Jagjit Singh Gilhotra; Sumu Simon; Konrad Pesudovs (SpringerOpen, 2017)
Abstract Background The lack of an appropriate retina-specific patient-reported outcome instrument restricts the understanding of the full impact of hereditary retinal diseases and other less common but potentially blinding acquired retinal diseases such as, vascular occlusions, epiretinal membrane, macular hole, central serous retinopathy and other vitreoretinopathies on quality of life. This study aims to explore the quality of life issues in people with hereditary retinal diseases and acquired retinal diseases to develop disease-specific patient-reported outcome instruments. Methods A qualitative research methodology to understand the lived experiences of people with retinal diseases was carried out. Data were collected through semistructured interviews. The coding, aggregation and theme development was carried out using the NVivo −10 software. Results Seventy-nine interviews were conducted with participants with hereditary retinal diseases (n = 32; median age = 57 years) and acquired retinal diseases (n = 47; median age = 73 years). We identified nine quality of life themes (domains) relevant to people with retinal diseases. Difficulty in performing important day-to-day activities (activity limitation) was the most prominent quality of life issue in the hereditary retinal diseases group whereas concerns about health, disease outcome and personal safety (health concerns) was the most prominent quality of life issue in the acquired retinal diseases group. Participants with hereditary retinal diseases had more issues with social interaction (social well-being), problems with mobility and orientation (mobility), and effect on work and finance (economic) than participants with acquired retinal diseases. On the contrary, participants with acquired retinal diseases reported more inconveniences (conveniences) than participants with hereditary retinal diseases, which were mostly attributed to treatment. Participants with hereditary retinal diseases were coping better compared to participants with acquired retinal diseases. Conclusions Our study found that participants with both hereditary and acquired retinal diseases are living with myriad of disease-specific quality of life issues. Many of these issues are completely different and unique to each disease group. Hence, these group of diseases would need separate patient-reported outcome instruments to capture the disease-specific quality of life impacts.